“Noah Fires an Arrow!” the Rise of Narrative Mechanics in Tabletop Role-playing Games 1979-1989 and the Importance of Archiving the Human Element - (:unkn) unknown (My University, 2020)
Tabletop role-playing games (TRPG) emerged out of the war gaming and science fiction subcultures in the mid-1970s. During the latter half of the 1970s these games shifted away from their combat focused wargaming roots to forge their own identity separate from miniature wargaming. In the 1980s the industry expanded rapidly and many of the new games focused their efforts on crafting narrative rather than combat based mechanics. It was this focus on narrative mechanics and unique settings which enabled the industry to both directly and indirectly engage with the socio political and cultural movements of the 1980s in Reagan’s America. This narrative focus highlights the importance of players actions in the collaborative storytelling effort but also their importance to the historical record. The What’s Your Origin Story (WYOS) archive aims to collect player’s stories through oral histories as well as an online journaling project. We aim to diversify the historical record as well as preserve the human element for future scholars in our field.
Keywords: 1980s; Community Archives; Cultural history; Games Studies; Oral history; Tabletop Role-playing Games